Systemic Failures in Educational Management and the Normalisation of Child Exploitation among Vulnerable Learners - Farid Khoeroni; Faricha Andriani; Taufikin Taufikin (Journal of Educational Management Research, 2026)
This study aims to analyse the exploitation of street children as a manifestation of dysfunctional educational management and weak coordination among educational organisations, rather than merely as a poverty-related social issue. Employing a qualitative phenomenological approach, data were collected through in-depth interviews, observations, and document analysis involving street children active around the Kriyan gas station area in Jepara. The data were analysed using an interactive model consisting of data reduction, data display, and conclusion verification. The findings reveal that child exploitation is sustained through normalised parental consent, institutional tolerance of child labour within schools, and community silence that morally legitimises these practices. Although children remain structurally enrolled in formal and non-formal education, they experience functional exclusion in the form of unequal learning time and persistent disruptions to the educational process. These conditions indicate a cycle of failure in educational management rooted in organisational complexity and weak ethical decision-making. This study contributes to educational management scholarship by introducing the concept of the educational complicity loop as an analytical framework, while offering practical implications for strengthening school leadership, improving cross-institutional coordination, and reinforcing ethical governance in education systems to better protect vulnerable learners.